Stress level and prescription of anxiolytic drugs in post-pandemic older adults in the city of Huancayo. 2023 - Lavado Morales , Ivar Jines (2024)
Objective: To determine the level of stress and prescription of anxiolytic drugs in post-pandemic elderly in the city of Huancayo. 2023. Material and Methods: Descriptive, non-experimental and cross-sectional design. Population: 4,250 older adults and a sample of 352 older adults. Results: The level of stress of post-pandemic older adults in the city of Huancayo, according to the EEP-10 scale, was found to be high stress with 1.84. Determined, at a Cronbach's Alpha = 0.828 and at a significance level α ˂ 0.05. The frequency of age 61-69 prevails at 33.5 %. The sex of the respondents prevails female. As for the employment status, mostly engaged in agriculture, retired and self-employed. The most commonly used anxiolytic drugs are clonazepam, alprazolam and diazepam. The anxiolytic drugs modified their sensation in the patient: fatigue, depression and apathy. The prescription for the consumption of anxiolytics was by a physician. Conclusions: The stress level of the older adult was a high stress level, the female sex prevails with higher stress, the prescription was by a physician. The most used anxiolytic is clonazepam.